Dynamics of Collaboration Among Work Units at Adi Soemarmo Airport in Serving Umrah Pilgrims - Kusuma, Regina Dwi Sekar; Nasution, Fauzia Fahmi Yuniarti (Advances In Social Humanities Research, 2025)
As providers of air transportation services, airport managers must ensure optimal operational services, which require efficient collaboration between various work units. This collaboration is vital for the service of Umrah pilgrims at Adi Soemarmo Airport, focusing on the security and safety of the pilgrims from different aspects by coordinating with relevant stakeholders. The availability of clean and safe facilities and areas that pilgrims pass through, both during departure and arrival, is essential. Officers need to be vigilant about maintaining the security and safety of Umrah pilgrims throughout their time at the airport. This research aims to explore the dynamics of collaboration between work units at Adi Soemarmo Airport and evaluate how these collaborations ensure the smooth running of Umrah pilgrim services. The study uses a qualitative exploratory approach to collect and analyze data in depth. Data collection methods include interviews, observations, documentation, and other techniques to gather contextual information. The results indicate that collaboration among work units for Umrah pilgrim services has been efficient and in line with established SOPs. Key units involved in these services include the Landside/Terminal Unit, Airside Unit, Aviation Security Unit, CIQ Unit, KKP Unit, Ground Handling, Transportation Agency, Religion, and Airlines. Coordination is facilitated through three media: HT, PABX, and Extend, with morning briefings serving as the primary form of collaboration. Pilgrims' luggage is collected a day before departure (H-1) and loaded onto the plane. Pilgrims go through two security checks and immigration during departure, while arrival involves customs and baggage claim procedures. Required documents include tickets, passports, Umrah visas, health certificates, and meningitis vaccines.